Revolution of CAR Engineering For Next-Generation Immunotherapy In Solid Tumors - Yu, Tao; Yu, Shao-kun; Xiang, Yan; Lu, Kai-Hua; Sun, Ming (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR)-T cells have enormous potentials for clinical therapies. The CAR-T therapy has been approved for treating hematological malignancies. However, their application is limited in solid tumors owing to antigen loss and mutation, physical barriers, and an immunosuppressive tumor microenvironment. To overcome the challenges of CAR-T, increasing efforts are put into developing CAR-T to expand its applied ranges. Varied receptors are utilized for recognizing tumor-associated antigens and relieving immunosuppression. Emerging co-stimulatory signaling is employed for CAR-T activation. Furthermore, other immune cells such as NK cells and macrophages have manifested potential for delivering CAR. Hence, we collected and summarized the last advancements of CAR engineering from three aspects, namely, the ectodomains, endogenous domains, and immune cells, aiming to inspire the design of next-generation adoptive immunotherapy for treating solid tumors.